Bioinspired MWCNT-reinforced alumina composite materials - Evers, K (2019)
Nacre, a ceramic composite found in seashells, has baffled scientists due to its extraordinary mechanical properties. Consequently, nacre has been a main source of inspiration to create strong and tough ceramic composites that mimic nacre’s microstructure. The precise microstructural features responsible for its unique combination of high strength and toughness are however debated, and efforts to mimic and improve upon nature’s design have not led to commercial applications of ceramic nacre-like composites.